Developing Energy Harvest Efficient Strategies with Microbial Fuel Cells - Serra, Pedro Miguel Domingos (2022)
Nowadays, thinking of energetic efficiency is to determine how to decrease consumption and to reuse resources. This is a major concern when addressing hydric resources. The consumption of drinking water is seeing an unaffordable growth and, although most of it is replenished to the environment, the water quality is affected by pollutants and impurities. As such, using wastewater, a by-product of our routine and way of life, as resource is an asset. Even more when thinking about the heightened energy costs of a wastewater treatment station. The hypotheses of this work show how to achieve this goal by using microbial fuel cells. The organic composition of this water increases its energy production potential, where the bacterial metabolism can be used to, simultaneously, produce energy and help to clean the water. This document is divided in 5 chapters. The strategic positioning of the theme happens in chapter 1. Chapter 2 explains how the main elements of microbial fuel cell technology can work and determine its operation. In chapter 3, the power management systems used with microbial fuel cells are presented and discussed, with the identification of optimization strategies. The second-to-last chapter corresponds to the experimental results discussion and validation, while focusing improved energy production efficiencies. The outputs of this chapter pilot the future work analysis on chapter 5, together with the main conclusions and research trends. The validity and usefulness of this work is cleared with an application example.